TYPES OF PHYSICAL EDUCATION AND THE TECHNOLOGIES OF ORGANIZATION OF MATTERS IN THE MODERN EDUCATION SYSTEM - Gafurjonovich, Maxsudov Valijon; Yaxshivayevich , Ermetov Erkinbay; Ravshanqizi , Jo’rayeva Ziyoda (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
While in the modern educational environment, it remains to be seen that lectures are a leading form of organization of higher education, its intensive development, its form and content. The type, form, content, and functional role of the lecture, in turn, determine the interaction between the trainee and the trainee.